Handbook of soilid waste management and waste minimization technologies - Cheremisinoff, Nicholas P . (Butterworth-Heinemann, 2003)
Source reduction and waste minimization. Environmental laws and regulatory drivers. Municipal solid waste. Landfill operations and gas enery recovery.